Upregulation of mesothelial genes in ovarian carcinoma cells is associated with an unfavorable clinical outcome and the promotion of cancer cell adhesion. Issue 9 (25th June 2020) - Ojasalu, Kaire; Brehm, Corinna; Hartung, Kristin; Nischak, Maximilian; Finkernagel, Florian; Rexin, Peter; Nist, Andrea; Pavlakis, Evangelos; Stiewe, Thorsten; Jansen, Julia M.; Wagner, Uwe; Gattenlöhner, Stefan; et al.
Abstract : A hallmark of ovarian high‐grade serous carcinoma (HGSC) is its early and massive peritoneal dissemination via the peritoneal fluid. It is generally believed that tumor cells must breach the mesothelium of peritoneal organs to adhere to the underlying extracellular matrix (ECM) and initiate metastatic growth. However, the molecular mechanisms underlying these processes are only partially understood. Here, we have analyzed 52 matched samples of spheroids and solid tumor masses (suspected primary lesions and metastases) from 10 patients by targeted sequencing of 21 loci previously proposed as targets of HGSC driver mutations. This analysis revealed very similar patterns of genetic alterations in all samples. One exception was FAT3 with a strong enrichment of mutations in metastases compared with presumed primary lesions in two cases. FAT3 is a putative tumor suppressor gene that codes for an atypical cadherin, pointing a potential role in peritoneal dissemination in a subgroup of HGSC patients. By contrast, transcriptome data revealed clear and consistent differences between tumor cell spheroids from ascites and metastatic lesions, which were mirrored by the in vitro adherence of ascites‐derived spheroids. The adhesion‐induced transcriptional alterations in metastases and adherent cells resembled epithelial–mesenchymal transition, but surprisingly also included the upregulation of a specific subset of mesothelial genes, such as calretinin (CALB2) and podoplanin (PDPN) . Consistent with this finding, calretinin staining was also observed in subsets of tumor cells in HGSC metastases, particularly at the invasive tumor edges. Intriguingly, a high expression of either CALB2 or PDPN was strongly associated with a poor clinical outcome. siRNA‐mediated CALB2 silencing triggered the detachment of adherent HGSC cells in vitro and inhibited the adhesion of detached HGSC cells to collagen type I. Our data suggest that the acquisition of a mesenchymal–mesothelial phenotype contributes to cancer cell adhesion to the ECM of peritoneal organs and HGSC progression. Abstract : Attachment of ovarian cancer cells to damaged mesothelium is a critical step in metastatic spread. This study suggests that cancer cell adhesion to the extracellular matrix (ECM) is linked to mutations in the atypical cadherin and tumor suppressor FAT3 in a subset of patients, as well as to a mesenchymal–mesothelial phenotype involving the upregulation of calretinin and podoplanin.